Peningkatan Kesadaran Keamanan Siber (Cyber Security Awareness) melalui Penyuluhan bagi Siswa Sekolah Menengah Pertama - Dwi Wahyudi; Radinal Fadli (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
The rapid growth of digital technology increases cyber threat risks for junior high school students. This community service activity aimed to enhance students' cyber security awareness and behavioral intentions through interactive counseling. The implementation method included multimedia presentations, threat simulations, and evaluations using pre-test and post-test designs with 40 students at SMP Islam Plus At-Tholibin. The evaluation instrument covered four behavioral scales: risky, conservative, risk exposure, and risk perception behavior. Results showed a significant shift in perspectives, with average scores increasing from 2.15 to 3.72. The N-Gain analysis yielded a score of 0.84, categorized as “High”. This proves that gamification and simulation approaches are effective in providing a deep understanding to recognize cyber threats from an early age. This activity is expected to serve as a model for sustainable education to build a cyber security culture within the school environment.